The Cauchy Problem to a Shallow Water Wave Equation with a Weakly Dissipative Term - Ying Wang; YunXi Guo (Abstract and Applied Analysis)
A shallow water wave equation with a weakly dissipative term, which includes the weakly dissipative Camassa-Holm and the weakly dissipative Degasperis-Procesi equations as special cases, is investigated. The sufficient conditions about the existence of the global strong solution are given. Provided that (1-∂x2)u0∈M+(R), u0∈H1(R), and u0∈L1(R), the existence and uniqueness of the global weak solution to the equation are shown to be true.